2021
DOI: 10.1177/1071181321651218
|View full text |Cite
|
Sign up to set email alerts
|

User Needs of Smart Home Services

Abstract: Technological advances have improved the functionality of smart home systems and services, enabling consumers to automate some of in-home tasks, enhance their safety and security, and save energy. Despite improved functionality, user adoption of many available products and services remains low. This phenomenon suggests that smart home technologies may not be meeting the needs of potential users. Furthermore, continued technological advancement combined with changes in people’s lifestyle and attitudes towards i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Lectures incorporating this word include "User Experience and Evaluation." This word appeared frequently in conference proceedings titles such as "Tele-Technology Evaluation and User Testing with Persons Aging with Long-Term Mobility Disabilities" (Wu et al, 2021), "Internet Accessibility for Blind and Visually-Impaired Users: An Evaluation of Official U.S. State and Territory COVID-19 Websites" (Hewitt & He, 2021), and "User Needs of Smart Home Services" (FakhrHosseini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Lectures incorporating this word include "User Experience and Evaluation." This word appeared frequently in conference proceedings titles such as "Tele-Technology Evaluation and User Testing with Persons Aging with Long-Term Mobility Disabilities" (Wu et al, 2021), "Internet Accessibility for Blind and Visually-Impaired Users: An Evaluation of Official U.S. State and Territory COVID-19 Websites" (Hewitt & He, 2021), and "User Needs of Smart Home Services" (FakhrHosseini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, ten potential areas of focus encompassing safety, convenience, self-care, and family care were identified. This set of focus areas was established based on a review of relevant past studies (FakhrHosseini et al (2021), the results of a large-scale online survey, and interviews with eleven participants of diverse backgrounds about their activities, pain points, and desires. Because this set of focus areas was still quite broad, it was analyzed in the context of existing relevant literature and reviewed by industry experts.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that many factors are involved in attracting a wider range of users to accept and adopt a technology. In an interview study, FakhrHosseini et al (2021) explored user needs of smart home devices and found interconnected and multi-purpose systems are among the top needs, which point to the importance of convenience, usefulness and simplicity. Holzinger, Searle, and Wernbacher (2011) empirically showed that the effect of previous exposure to technology has positive impacts on acceptance of it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 23 concepts were identified based on (FakhrHosseini et al, 2021) and (Lee et al, 2020) as potential emerging technologies and services of interest. The concepts are shown in Figure 1.…”
Section: Study Proceduresmentioning
confidence: 99%